2014
DOI: 10.1155/2014/906965
|View full text |Cite
|
Sign up to set email alerts
|

Global Consequences of Liver Ischemia/Reperfusion Injury

Abstract: Liver ischemia/reperfusion injury has been extensively studied during the last decades and has been implicated in the pathophysiology of many clinical entities following hepatic surgery and transplantation. Apart from its pivotal role in the pathogenesis of the organ's post reperfusion injury, it has also been proposed as an underlying mechanism responsible for the dysfunction and injury of other organs as well. It seems that liver ischemia and reperfusion represent an event with “global” consequences that inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
237
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(249 citation statements)
references
References 124 publications
(154 reference statements)
8
237
1
3
Order By: Relevance
“…After the introduction of vascular control techniques during hepatic surgery, liver ischemia and reperfusion has been recognized as one of the key elements that contributes to postoperative morbidity and mortality. Liver dysfunction and failure are serious postoperative complications which may ensue as a result of reperfusion injury 24 .…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the introduction of vascular control techniques during hepatic surgery, liver ischemia and reperfusion has been recognized as one of the key elements that contributes to postoperative morbidity and mortality. Liver dysfunction and failure are serious postoperative complications which may ensue as a result of reperfusion injury 24 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…In addition, reactive oxidant species (ROS) can be found inducing oxidative stress to the liver as well as to distant organs. ROS activate Kuppfer cells, promoting even further ROS as well as cytokine production 24 . Reactive oxygen species are largely generated from mitochondrial energy metabolism via oxidative phosphorylation in the respiratory chain.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Thus, ischemic tissue becomes primed for sustaining further damage upon the reversal of ischemia. 1,60,61 Tissue priming is at least partly caused by depletion of intracellular antioxidant defenses during the initial ischemic event. 60 Upon reperfusion with oxygenated blood, ROS production is further stimulated, both by the presence of O 2 and by the normal inflammatory cascade set in motion by tissue injury.…”
Section: Systemic Effects Of Hyperoxiamentioning
confidence: 99%
“…This has global consequences because the inflammatory cascade initiated by ischemia-reperfusion injury causes remote damage to other organ systems. 61 Mounting clinical and preclinical evidence indicates that hyperoxia during cardiopulmonary bypass, 58 following cardiac arrest, 62 liver ischemia, 63 and brain ischemia, 64 provokes multi-organ damage, suggesting that hyperoxia should be avoided whenever possible. A meta-analysis of preclinical studies of cardiac arrest 65 found that resuscitation with an F IO 2 of 1 sustained for 60 min after the return of spontaneous circulation produced significantly greater neuronal damage and worse neurologic deficits compared with an F IO 2 of 0.21 or titrated to maintain normal arterial oxygenation.…”
Section: Systemic Effects Of Hyperoxiamentioning
confidence: 99%
“…Oxidative stress (free radical damage) has been found to be a major factor in a number of major human health problems including heart disease [1][2][3], diabetes [4,5], intestinal diseases [6][7][8], liver disease [9], renal disease [10,11] and obstructive bladder dysfunction [12][13][14][15]. In virtually all of these oxidative stress-linked dysfunctions, antioxidants have proven to be very valuable in their treatment [13,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%